Clonal heterogeneity influences drug responsiveness in renal cancer assessed by ex vivo drug testing of multiple patient‐derived cancer cells. Issue 6 (4th November 2018) - Saeed, Khalid; Ojamies, Poojitha; Pellinen, Teijo; Eldfors, Samuli; Turkki, Riku; Lundin, Johan; Järvinen, Petrus; Nisen, Harry; Taari, Kimmo; af Hällström, Taija M.; Rannikko, Antti; Mirtti, Tuomas; et al.
Abstract : Renal cell cancer (RCC) has become a prototype example of the extensive intratumor heterogeneity and clonal evolution of human cancers. However, there is little direct evidence on how the genetic heterogeneity impacts on drug response profiles of the cancer cells. Our goal was to determine how genomic clonal evolution impacts drug responses. Finding from our study could help to define the challenge that clonal evolution poses on cancer therapy. We established multiple patient‐derived cells (PDCs) from different tumor regions of four RCC patients, verified their clonal relationship to each other and to the uncultured tumor tissue by genome sequencing. Furthermore, comprehensive drug‐sensitivity testing with 460 oncological drugs was performed on all PDC clones. The PDCs retained many cancer‐specific copy number alterations and mutations in driver genes such as VHL, PBRM1, PIK3C2A, KMD5C and TSC2 genes. The drug testing highlighted vulnerability in the PDCs toward approved RCC drugs, such as the mTOR‐inhibitor temsirolimus, but also novel sensitivities were uncovered. The individual PDC clones from different tumor regions in a patient showed distinct drug–response profiles, suggesting that genomic heterogeneity contributes to the variability in drug responses. Studies of multiple PDCs from a patient with cancer are informative for elucidating cancer heterogeneity and for the determination on how the genomic evolution is manifested in cancer drug responsiveness. This approach could facilitate tailoring of drugs and drug combinations to individual patients. Abstract : What's new? The comparison of drug responses among multiple variants of patient‐derived cells (PDCs) exhibited the impact of intra‐tumor genomic heterogeneity, as the individual PDCs from different tumor regions showed distinct drug sensitivity profiles. These data illustrate an approach that could facilitate the design of effective personalized drug combinations needed to target multiple subclones in cancer and for elucidating pharmacogenomic biomarkers.